2018
DOI: 10.1103/physrevc.98.061302
|View full text |Cite
|
Sign up to set email alerts
|

Energy spectrum of neutron-rich helium isotopes: Complex made simple

Abstract: We demonstrate that the intricate energy spectrum of neutron-rich helium isotopes can be straightforwardly described by taking advantage of the low-energy properties of neutron-neutron interaction and the scale separation that is present in diluted dripline systems. By using arguments based on the halo effective field theory, we carry out a parameter reduction of the complex-energy configuration interaction framework in the spd space, including resonant and scattering states. By adjusting only one parameter, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 80 publications
1
20
0
Order By: Relevance
“…Common to all these approaches is that a configuration space interaction that is given in terms of SHO matrix elements is expanded on a basis containing SHO and Berggren states, hence it is still an open question how a direct implementation of the interactions in a basis with continuum degrees of freedom might modify existing results. It is worth noting that such a construction has been achieved for phenomenological GSM interactions that have been tuned for light nuclei [217][218][219][220][221][222]. In light nuclei, the NCSMC has been applied with impressive success to describe a variety of exotic nuclei with up to three-cluster structures.…”
Section: Toward the Drip Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Common to all these approaches is that a configuration space interaction that is given in terms of SHO matrix elements is expanded on a basis containing SHO and Berggren states, hence it is still an open question how a direct implementation of the interactions in a basis with continuum degrees of freedom might modify existing results. It is worth noting that such a construction has been achieved for phenomenological GSM interactions that have been tuned for light nuclei [217][218][219][220][221][222]. In light nuclei, the NCSMC has been applied with impressive success to describe a variety of exotic nuclei with up to three-cluster structures.…”
Section: Toward the Drip Linesmentioning
confidence: 99%
“…sections 2.3.8 and 3.2.4), as well as the GSM Coupled Channel (GSM-CC) approach, which was developed to describe reactions between light projectiles and targets that are treated in the GSM with a core [221,328,329]. Thus far, applications of the GSM-CC have been based on phenomenological valence-space interactions, but new efforts are underway to directly construct suitable Hamiltonians based on EFT principles [220,330], or derive the effective interactions from chiral forces with the techniques discussed in section 2.3 (see [214,215]). Of course, the GSM-CC ideas could also be applied to the No-Core GSM [153,155,218], although the computational complexity would limit such an approach to light nuclei.…”
Section: Interfacing With Reaction Theorymentioning
confidence: 99%
“…We want to mention here that a similar approach was employed in Ref. [29] to construct an effective neutronneutron interaction for the description of the helium isotopic chain in the Berggren basis. In that case, using only the central term V 01 c , a good reproduction of weaklybound and unbound states in helium nuclei was achieved.…”
Section: B Gamow Shell Model Hamiltonianmentioning
confidence: 99%
“…By means of the principal-component analysis, it was concluded that a very reasonable description of energies of 6 ≤ A ≤ 9 nuclei (rms deviation from experiment of 250 keV) could be achieved with only four interaction parameters. In the follow-up paper [29], carried out in the spd space, experimental energies and widths of 5−8 He could be reproduced within tens of keV precision by adjusting only one parameter (the strength of spinsinglet central neutron-neutron term). In this work, we construct the minimal GSM model to describe binding energies and spectra of 5 ≤ A ≤ 11 nuclei in the sp space by carrying out simultaneous optimization of the corenucleon potential and the valence two-body interaction with the mass-dependent interaction scaling to effectively account for the missing three-body forces.…”
mentioning
confidence: 99%
“…These drawbacks include the scaling behavior as a function of mass number, the convergence of observables as a function of basis states, the validity of many-body truncations, and constraints regarding which nuclear interactions can be used. A special but related challenge is the development, within the basic model, of approaches accounting for the coupling to the continuum-these are mandatory to describe, for instance, weakly bound nuclear systems [18,19].…”
Section: Introductionmentioning
confidence: 99%